Nonsense Mutation (c.1425G>A-p.Trp475Ter) Associated with Oculocutaneous Albinism Type 1A (OCA1A) in Yogyakarta - Karmilah, Karmilah; Dian Pratiwi, Arini; Nur Handayani, Niken Satuti (Fakultas Kedokteran Universitas Brawijaya, 2025)
Oculocutaneous Albinism (OCA) is a disorder characterized by impaired melanin synthesis that leads to hypopigmentation of the skin, hair, and eyes, accompanied by distinct ocular abnormalities. The global prevalence of all forms of albinism is approximately 1 in 17,000 individuals, and OCA1 is the most common type. OCA1 results from mutations in the TYR gene and specifically involves a complete loss of tyrosinase enzyme function, resulting in a total absence of pigment in the skin, eyes, and hair. This case report describes two male patients with congenital symptoms of extremely light or depigmented skin and hair. Both presented with white eyelashes and eyebrows, grayish irises, and ocular abnormalities, including nystagmus, photophobia, and strabismus. The analysis showed a genetic variant in the exon of the TYR gene with the mutation variant c.1425G>A/p.Trp475Ter and was found to be a nonsense mutation.